2019
DOI: 10.1111/dme.13939
|View full text |Cite
|
Sign up to set email alerts
|

Decision aids for people with Type 2 diabetes mellitus: an effectiveness rapid review and meta‐analysis

Abstract: Aims To perform a rapid review and meta-analysis of randomized controlled trials (RCTs) evaluating patient decision aids (PtDAs) for people with Type 2 diabetes mellitus. Methods We searched Medline and the Cochrane Library for RCTs assessing PtDAs in people with Type 2 diabetes. PtDAs were defined as tools designed to help people engage in decision-making about healthcare options, such as making treatment choices or setting therapeutic goals. The study selection process was facilitated by an automated screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…38 In recent years, it has been inspiring to see studies using ML-aided methods, improved search lters, as well as crowdsourcing projects to replace conventional manual screening during SR researches. 10,[39][40][41] However, the ultimate goal should be a comprehensive database containing well-structured and indexed information concerning the study type, research details, outcome data, etc. Various methods have been employed to identify such sets of information from published studies.…”
Section: Discussionmentioning
confidence: 99%
“…38 In recent years, it has been inspiring to see studies using ML-aided methods, improved search lters, as well as crowdsourcing projects to replace conventional manual screening during SR researches. 10,[39][40][41] However, the ultimate goal should be a comprehensive database containing well-structured and indexed information concerning the study type, research details, outcome data, etc. Various methods have been employed to identify such sets of information from published studies.…”
Section: Discussionmentioning
confidence: 99%
“…neuropathy, retinopathy, nephropathy, diabetic foot, stroke, cardiovascular and peripheral vascular diseases) for improvement of the QoL. Patient decision-support aids have been used for various purposes for decision making in people with diabetes about options like the treatment choices or setting the therapeutic goals and have been proven in improving the quality of decision making and increase of knowledge transfer [7]. The amount of data each person living with diabetes can generate is huge and can amount to 1 million gigabytes but most of the data is unstructured [5].…”
Section: Role Of Ai In Diabetesmentioning
confidence: 99%
“…Although a number of PtDAs related to aspects of diabetic disease have been evaluated, there has been no review of the overall efficacy on these PtDAs in diabetes. A recent article (Karagiannis et al, 2019) revealed that PtDA had a significant effect on reducing decisional conflict and improving knowledge among patients with T2DM. However, this meta‐analysis implemented a rapid review approach, which only searched two major databases, and risk of bias assessment by a single reviewer.…”
Section: Introductionmentioning
confidence: 99%